Wykładnia ustawowej przesłanki „zgłoszenie wniosku we właściwym czasie” - Stefanicki, Robert (Uniwersytet Wrocławski. Wydział Prawa, Administracji i Ekonomii, 2018)
The commentary on Bankruptcy Law in the light of the Tax Ordinance regarding the tax responsibility of members of the management board in respect of public obligations leads to the conclusion that they are required to file bankruptcy petition at such time that the objective – proportionate satisfaction of creditors' claims by clearance proceedings aiming at administration or winding-up: bankruptcy; restructuring – should not be eradicated. Therefore, it is of particular importance from this perspective to set an adequate deadline for the submission of the proposal by the management board members. These problems remain in synergy with the requirements of professional diligence of these officers
Keywords: Tax Ordinance; institution of execution proceedings against the company; circumstance exemptions; bankruptcy petition was filed in due time; the execution against the company’s assets has proven ineffective